Evaluation of extruded and germinated sorghum as a potential ingredient in dog and cat diets - Bailey, Katelyn (Kansas State University, 2024)
Sorghum has many unique features that can be utilized in the pet food industry. However, its growth is hindered by outdated livestock literature and negative connotations. The aim of this thesis was to evaluate various sorghum accessions and preparations as an ingredient in extruded and raw pet foods for utilization by dogs and cats. The first study determined the processability of different sorghum pericarp varieties (white sorghum A, white sorghum B, burgundy sorghum, and sumac sorghum) compared to four small grains (rice, barley, oats, and millet). All four sorghum varieties produced well-expanded kibbles providing evidence for a good substitution for other small grains. Digestibility and oxygen radical antioxidant capacity (ORAC) of the sorghum containing diets were evaluated with 12 adult beagles in a 4 × 4 Latin square design experiment. Dietary treatments comprised 50% of white sorghum A or B, burgundy sorghum, or rice (as the control). No differences were observed in crude protein and fat apparent total tract digestibility (P>0.05). Furthermore, ORAC values were similar among all treatments (P=0.4928). Dogs fed the rice diet had higher plasma cholesterol levels compared to dogs fed the three sorghum treatments (P=0.0007); otherwise, diet had little influence on humoral constituents. This suggests that sorghum may be a good substitute for rice in canine diets. Consumers are demanding “natural” and less processed – even raw diets for their pets. Raw diets consist of raw meat, bones, fruits, and vegetables. However, they cannot undergo any heating to be considered “raw.” Because carbohydrates typically require cooking, they are not commonly included in raw diets. Germination may solve this problem as it mobilizes the nutrients within the plant. To evaluate this, five common cereal grains (corn, millet, sorghum, soy, and wheat) were selected for evaluation. Seeds were germinated to initial sprout eruption and also allowed to grow into microgreens and then compared to the raw seeds. In general, a decrease in ash, fat (except for soy), resistant starch (except for soy), phytic acid (exception for corn and soy) and increases in in vitro protein digestibility (exception for wheat) were observed in the germinated seeds compared to their raw seeds. From this, sorghum was selected to evaluate further for seed growth, diet processing, and animal utilization. Sprouts and microgreens were grown in a commercial microgreen tower (Throckmorton Hall, Kansas State University). Growth optimization was undertaken to determine the best substrate and seed density. Once a protocol was developed sprouts and microgreens were grown for food production. Raw diets containing 30% seeds were produced in the laboratory and then diets were pasteurized at high pressure (HPP) and verified for microbial safety at a commercial laboratory. Eleven shorthair cats were enrolled in a replicated incomplete 4 × 4 Latin square designed feeding study that consisted of 5 d adaptation followed by 5 d collection in each of the 4 periods. Treatments included raw sorghum, cooked sorghum, sprouts, and microgreens. Cats fed the sprouted and microgreen-based diets had similar dry matter, organic matter, and gross energy apparent total tract digestibility to the raw sorghum, and all were lower digestibility compared to the cats fed the cooked sorghum diet (P < 0.05). Among treatments, no differences were observed in protein digestibility (P> 0.05). However, fecal scores were the major difference in this study as cats fed the raw and sprouted diets had more diarrhea and loose stools compared to cats fed the microgreen and cooked diets. Further evaluation is needed on sorghum microgreens as an ingredient in raw diets. Overall, sorghum is a good substitute for other common grains as it can process well in an extruded diet, provides high levels of polyphenols, and provides potential for new products in raw diets.
Keywords: Sorghum; Pet food; Extruded; Raw; Germinated